Skeletal and molecular findings in 51 Cleidocranial dysplasia patients from Turkey. Issue 8 (13th May 2021) - Berkay, Ezgi Gizem; Elkanova, Leyla; Kalaycı, Tuğba; Uludağ Alkaya, Dilek; Altunoğlu, Umut; Cefle, Kıvanç; Mıhçı, Ercan; Nur, Banu; Taşdelen, Elifcan; Bayramoğlu, Zuhal; Karaman, Volkan; Toksoy, Güven; et al.
Abstract: Loss or decrease of function in runt‐related transcription factor 2 encoded by RUNX2 is known to cause a rare autosomal‐dominant skeletal disorder, cleidocranial dysplasia (CCD). Clinical spectrum and genetic findings in 51 CCD patients from 30 unrelated families are herein presented. In a majority of the patients, facial abnormalities, such as delayed fontanel closure (89%), parietal and frontal bossing (80%), metopic groove (77%), midface hypoplasia (94%), and abnormal mobility of shoulders (90%), were recorded following clinical examination. In approximately one‐half of the subjects, wormian bone (51%), short stature (43%), bell‐shaped thorax (42%), wide pubic symphysis (50%), hypoplastic iliac wing (59%), and chef's hat sign (44%) presented in available radiological examinations. Scoliosis was identified in 28% of the patients. Investigation of RUNX2 revealed small sequence alterations in 90% and gross deletions in 10% of the patients; collectively, 23 variants including 11 novel changes (c.29_30insT, c.203delAinsCG, c.423 + 2delT, c.443_454delTACCAGATGGGAinsG, c.505C > T, c.594_595delCTinsG, c.636_637insC, c.685 + 5G > A, c.1088G > T, c.1281delC, Exon 6–9 deletion) presented high allelic heterogeneity. Novel c.29_30insT is unique in affecting the P1‐driven long isoform of RUNX2, which is expected to disrupt the N‐terminal region of RUNX2; this was shown in two unrelated phenotypically discordant patients. The clinical findings highlighted mild intra‐familial genotype–phenotype correlation in our CCD cohort.